The Role of the Gampong Government in Development in Gampong Jawa, Kuta Raja District, Banda Aceh City - Ibnu Sovian; Syafei Ibrahim; Salahuddin (INDONESIAN JOURNAL OF SOCIAL POLITIC AND POLICY STUDIES, 2025)
The role of the village government in development and the process of preparing income and expenditure budgets in Gampong Jawa, the Village Government has not implemented it well, can be seen through the establishment of regulations and the development of sources of income. implementation of village development, the stage of construction of facilities and infrastructure has not been supported and the community has not felt the benefits, especially economic development and use of natural resources. Problem formulation 1). How is development planning and supervision in Gampong Jawa? How is development and community training carried out in Gampong Jawa? Research Objectives 1). To find out and analyze development planning and supervision in Gampong Jawa. 2). To find out and analyze the implementation of development and community training in Gampong Jawa. The research method uses a qualitative approach. Data collection techniques use (1). Observation (2). Interview (3). Documentation. The results of research, planning in budget management, weaknesses in community proposals are still weak, supervision carried out by the community in Gampong Jawa is still very low, this is due to lack of community participation, lack of access to information provided by the Gampong government to the community, causing weak supervision carried out by the community towards the Gampong government, the implementation of village development has not gone well, this is because the Gampong government has not been able to utilize existing natural resources, and development of the Gampong community is carried out by the Gampong government as a manifestation of the government's role is still very weak, especially the role of the Gampong government in community development.